Ignorance under attitudes - Elliot, Patrick D.; Kobayashi, Filipe Hisao (Proceedings of the Amsterdam Colloquium, 2024)
Yablo (2014) observed that Ann and Beth agree that p or q conveys that p and q are both compatible with the beliefs of Ann and Beth. While Yablo argued for a radical departure from possible world semantics, we propose that this is due to local pragmatic reasoning. We frame our proposal within Update Semantics and develop a system where p or q requires the context to be compatible with both p and q. When disjunction is unembedded, our system yields ignorance inferences. Yablo’s puzzle is accounted for because, under attitude verbs the requirement is imposed in the complement clause’s local context.